1998
DOI: 10.1093/oxfordjournals.aje.a009396
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lung Cancer in Young Adults

Abstract: Risk factors for early onset of lung cancer are relatively unknown. In a case-control study, carried out in Germany between 1990 and 1996, the effects of smoking and familial aggregation of cancer were compared in 251 young cases and 280 young controls (< or = 45 years) and in 2,009 older cases and 2,039 older controls (55-69 years). The male/female ratio was 2.6/1 in young patients and 5.6/1 in older patients. Adenocarcinomas were more frequent in young men than in older men (41 % vs. 28%). Duration of smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
92
2
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 31 publications
8
92
2
2
Order By: Relevance
“…A number of studies have evaluated the influence of family history of cancer on subsequent lung cancer [12][13][14][15][16][17][18]. Family history of cancer, particularly lung cancer in younger first-degree relatives has been shown in some studies to be a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have evaluated the influence of family history of cancer on subsequent lung cancer [12][13][14][15][16][17][18]. Family history of cancer, particularly lung cancer in younger first-degree relatives has been shown in some studies to be a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an increase in risk with a reported familial history of reproductive cancer [12], others with reported family history of any cancer [13,15], while others have found an increased lung cancer risk in those with a reported excess of familial lung cancer [14,16]. Two studies [17,18] found a significant increase in risk with reported family history of lung cancer only for younger patients (e.g., only for patients aged less than 40 or 45). Odds ratios tend to be in the 1.5-3.0 range.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies (Schwartz et al, 1996;Wu et al, 2004;Matakidou et al, 2005) selected the age of 60 years as the cutoff between younger and older subjects, (pooled RR 4.39; 95% CI: 1.33 -14.42), three 55 years (Osann, 1991;Wu et al, 1996;Etzel et al, 2003) (pooled RR 1.10; 95% CI: 0.73 -1.65), two 50 years (Tsugane et al, 1987;Bromen et al, 2000) (pooled RR 1.68; 95% CI: 0.28 -10.12) and one study (Kreuzer et al, 1998) selected 45 years (RR 2.60; 95% CI: 1.10 -6.15).…”
Section: Case -Control Studiesmentioning
confidence: 99%
“…In all, 31 studies were identified that provided risks of lung cancer stratified by family history of the disease (Tokuhata and Lilienfeld, 1963a, b;Lynch et al, 1982;Ooi et al, 1986;Samet et al, 1986;Gao et al, 1987;Kramer et al, 1987;Sellers et al, 1987;Tsugane et al, 1987;Horwitz et al, 1988;Wu et al, 1988Wu et al, , 1996McDuffie et al, 1989;Wu-Williams et al, 1990;Liu et al, 1991;McDuffie, 1991;Osann, 1991;Shaw et al, 1991;Pavlakou et al, 1993;Schwartz et al, 1996Schwartz et al, , 1999Wang et al, 1996;Brownson et al, 1997;Kreuzer et al, 1998;Mayne et al, 1999;Bromen et al, 2000;Wunsch-Filho et al, 2002;Etzel et al, 2003;Wu et al, 2004;Jin et al, 2005;Matakidou et al, 2005). Three studies (Lynch et al, 1982;Sellers et al, 1987;Schwartz et al, 1999) were excluded from the review as the same data were duplicated in subsequent studies.…”
Section: Case -Control Studiesmentioning
confidence: 99%
“…Several studies have reported a slight increase of risk for relatives of lung cancer cases (Tokuhata and Lilienfeld, 1963;Mulvihill, 1976;Ooi et al, 1986;Bromen et al, 2000). Some of these, however, were limited to special groups such as nonsmokers or women, and this may have contributed to the different risks obtained (Schwartz et al, 1996;Wu et al, 1996;Brownson et al, 1997;Kreuzer et al, 1998;Pools et al, 1999). We have used improved modelling techniques to test the hypothesis that in Xuan Wei County, lung cancer cases are more likely than controls to have an affected relative.…”
mentioning
confidence: 99%